2000
DOI: 10.1590/s1516-35982000000400024
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da temperatura ambiente e da restrição alimentar sobre o desempenho e a composição da carcaça de frangos de corte

Abstract: RESUMO -O objetivo deste experimento foi estudar os efeitos da temperatura ambiente e da restrição alimentar sobre o desempenho produtivo, o rendimento das carcaças e dos cortes nobres e os teores de gordura, água e proteína das carcaças e os teores de glicogênio do fígado de frangos de corte em diferentes condições ambientais. O delineamento experimental usado foi em blocos casualizados, em esquema fatorial 5 x 2 (programa alimentar e sexo) com duas repetições dentro de cada ambiente e 14 aves por unidade exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
5
0
20

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 9 publications
7
5
0
20
Order By: Relevance
“…However, Dale & Fuller (1980) found better FCR with the dietary addition of 8% fat as compared to 2.25% in birds submitted to CHS. The lack of environmental effect found in the present study is consistent with Lana et al (2000), who also did not find FCR differences in birds submitted to 31°C as compared to those kept at 25°C. This was attributed to the proportional drop in feed intake and weight gain.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, Dale & Fuller (1980) found better FCR with the dietary addition of 8% fat as compared to 2.25% in birds submitted to CHS. The lack of environmental effect found in the present study is consistent with Lana et al (2000), who also did not find FCR differences in birds submitted to 31°C as compared to those kept at 25°C. This was attributed to the proportional drop in feed intake and weight gain.…”
Section: Resultssupporting
confidence: 93%
“…At the end of the experiment, average weight of birds under CHS was 6% lower than those under TNE, which was also observed by Ribeiro et al (2001a), who submitted birds to cyclic heat stress for a longer period (21 to 56 days of age). Oliveira Neto et al (2000), Lana et al (2000), and Howlider & Rose (1987) also found lower growth rates and final weight in CHS birds. Bonnet et al (1997) reported a 50% reduction in weight gain of birds submitted to chronic stress at 32°C as compared to birds kept in thermoneutral environment of 22°C, after three weeks.…”
Section: Resultsmentioning
confidence: 86%
“…The feed intake values obtained in the MH (36 ºC) and SH (39 ºC) treatments are in agreement with the results of Lana et al (2000). The authors found that, under high temperatures, broilers consume less feed and gain less weight, as function of lower feed intake, and that high BGTHI values cause worse broiler performance.…”
Section: Thermal Environmentsupporting
confidence: 83%
“…O nível energético das rações e a temperatura ambiente influenciam o desempenho e a composição da carcaça de frangos de corte, daí a importância de se tratarem conjuntamente os fatores dietéticos e climáticos (Lana et al, 2000). De acordo com Silva Jr. et al (2002), dependendo da magnitude e da duração do estresse térmico, poderão ocorrer desde pequenos decréscimos no ganho de peso até prostração e morte dos animais.…”
Section: Introductionunclassified
“…De acordo com Lana et al (2000), no entanto, são de 35; 32; 29; e 23ºC para a segunda, terceira, quarta e quinta semanas de vida. Segundo esses autores, a temperatura ambiente é o fator físico que mais afeta o desempenho de frangos de corte, pois influencia o consumo de ração, o ganho de peso e a conversão alimentar.…”
Section: Introductionunclassified